Moderating Role of Job Satisfaction on The Relation between Participative Leadership Styles and Performance in a Petrochemical Company - Kahpi, Heri Sapari; Khairusy, Mirza Abdi; Abidin, Zaenal; Salam, Anis Fuad (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2020)
The implementation of the participative leadership style has been positive on the increase in employee performance. However, how it works in an extraction and refining petrochemical-firm context is still elusive. This study investigates how a participatory leadership style may support employee performance as moderated by Job Satisfaction. Primary data from all 85 HRD employees in Cilegon Petrochemical Company is selected as a database. This study computes the relationships using the PLS-SEM procedure. This study proves that participative leadership style variables significantly influence employee performance. Job satisfaction has a significant positive effect on employee performance, and job satisfaction moderates the effect of participative leadership style on employee performance.